Does the Electronic Structure of Möbius Annulenes Follow Heilbronner's Ideas?. Issue 23 (31st October 2018) - Karadakov, Peter B.; Cooper, David L.
Abstract: It is shown, on the example of the monocyclic cyclononatetraenyl cation, C 9 H 9 +, that the fully‐variational optimization of modern ab initio wavefunctions based on spin‐coupled generalized valence bond (SCGVB) theory vindicates, in a surprising level of detail, essential features of Heilbronner's ideas for the electronic structure of Möbius annulenes such as the arrangement of overlapping carbon 2p atomic orbitals along a Möbius strip, leading to a phase inversion between the first and last orbitals. In the SCGVB description, the aromaticity of this Möbius system with eight π electrons follows from the extensive resonance between VB structures. Abstract : Was Heilbronner right ? In 1964 Heilbronner came up with the idea of a congugated cycle twisted in a Möbius ring and described it using simple Hückel molecular orbitals. Advanced spin‐coupled generalized valence bond (SCGVB) calculations on C9 H + 9 provide a surprisingly clear vindication of this intuitive and very useful concept, showing a set of overlapping single‐electron orbitals with a single negative overlap (see picture)